Establishment of a highly sensitive cell-based assay for screening of hypoxia-inducible factor regulators - Liew, Sien-Yei; Abd-Aziz, Noraini; Stanbridge, Eric J; Yusoff, Khatijah; Shafee, Norazizah; Mustafaa, Suhaili (The Malaysian Society For Biochemistry and Molecular Biology, 2023)
Cell-based assay is a powerful tool in the fields of drug discovery. One of the main targets of drug development is transcription factors. Hypoxia-inducible factors (HIFs) are transcription factors involved in cellular oxygen homeostasis and associated with disease pathophysiology. Currently, a highly sensitive cell-based assay to measure HIF activity is still lacking. Using luciferase reporter constructs, we developed a highly sensitive, stable reporter cell line for monitoring the activity of HIF. Four copies of hypoxia response element (HRE) of the erythropoietin (EPO) gene, which is one of the targets of HIF, were used to drive the expression of the luciferase reporter. This stable reporter cell line gave a 500-fold increase in the luciferase signal in hypoxia compared to a normoxia condition. This robust increase in hypoxia response is crucial to ensure consistency and reproducibility of HIF assay results while reducing the overall assay cost. The establishment of this highly sensitive cell-based HIF assay may help expedite research in the discovery of HIF regulatory drugs.